Spectroscopic characterization, DFT studies, molecular docking and cytotoxic evaluation of 4‐nitro‐indole‐3‐carboxaldehyde: A potent lung cancer agent. Issue 1 (20th August 2020) - Christopher Jeyaseelan, S.; Milton Franklin Benial, A.
Abstract: The 4‐nitro‐1H‐indole‐carboxaldehyde (NICA) molecule was characterized experimentally using FT‐IR, FT‐Raman and UV‐Vis spectra, and it was studied theoretically using DFT calculations. The optimized structure of the NICA molecule was determined by DFT calculations using B3LYP functional with cc‐pVTZ basis set. The electron localization function (ELF) and local orbital localizer (LOL) studies were performed to visualize the electron delocalization in the molecule. The experimental and theoretical wavenumbers of the title molecule were assigned using VEDA 4.0 program. The charge delocalization and stability of the title molecule were investigated using natural bond orbital (NBO) analysis. Frontier molecular orbitals (FMOs) and related molecular properties were calculated. UV‐Vis spectrum was calculated theoretically and validated experimentally. The reactive sites of the molecule were studied from the MEP surface and Fukui function analysis. The molecular docking analysis reveals that the NICA ligand shows better inhibitory activity against RAS, which causes lung cancer. The in vitro cytotoxic activity of the molecule against human lung cancer cell lines (A549) was determined by MTT assay. Thus, the NICA molecule can be used as a potential candidate for the development of the drug against lung cancer.